Appointing the Proper Operating Variables for Efficient Air-Cooled LiBr-Water Absorption Refrigerator - Shihab, Abdulwadood Salman (Basrah Journal for Engineering Sciences, 2009)
The aim of the present study is to perform analytical simulation for the single-effect LiBr- water absorption refrigerating system (ARS) in order to scan for all possibilities of operating the cycle among most available operating variables to obtain the best performance and determine what are the proper parameter needed to be changed so that the refrigerator can operate using ambient air instead of water and cooling tower accessories to dissipate the hear at the condenser and absorber. The COPs of the cycle was obtained as a function of the different temperature of the cycle and solution concentration. The performance characteristics of the cycle were examined by changing the temperature of the heating source supplied at the generator, the temperatures at the condenser, absorber, and evaporator. It can be concluded that the concept of air cooled absorption chiller is feasible with coefficient of performance of 0.43 10 0.79 depending on the evaporator temperature for any cooling capacity in some applications, where the chilled water supply temperature is not necessary to be too cold.